Progress of Dicyanomethylene-4H-Pyran Derivatives in Biological Sensing Based on ICT Effect - Hou, Ting-Ting; Cai, Yi; Zhang, Zhen-Yu; Wang, Cai-Yun; Tang, Ying-Hao; Zhu, Ming-Qiang; Wang, Ya-Long (Frontiers in Chemistry, 2022)
As one of the typical fluorescent cores, dicyanomethylene-4H-pyran (DCM) derivatives exhibit excellent photophysical and photochemical properties, such as large Stokes shift, excellent light stability, tunable near infrared (NIR) emission etc. The luminescence mechanism of DCM probes mainly depends on the intramolecular charge transfer (ICT). Hence, by regulating the ICT process, the probes can specifically act on the target molecule. Accordingly, a series of NIR DCM probes have been constructed to detect the ions, reactive oxygen species (ROS) and biological macromolecules in cells. However, there is no relevant review to summarize it at present. This minireview mainly summarizes the NIR DCM probes based on ICT effect and their applications in biosensor and biological imaging in recent years. This will be beneficial to innovatively construct new DCM probes and actively promote their application in the future.